Recommendation System for Prospective Bride and Groom Using Cosine Similarity Algorithm - Apriliya Kurnianti; Pascal Pahlevi; Inayah Mufidah (Universitas Muhammadiyah Yogyakarta, 2023)
Ta'aruf is an introductory process intended for getting to know each other between two individuals which is expected to continue at the marriage level. Forum ta'aruf Padi Melati is an institution under the Regional Leadership of Muhammadiyah Bantul that aims to become a medium for cadres Nasyi'atul Aisyiyah and Muhammadiyah Youth in finding a life partner. The ta'aruf process carried out by the current Forum ta'aruf Padi Melati is still carried out using information exchange via WhatsApp through forum leaders where the candidates will send biodata and criteria for the desired partner. The purpose of this study was to design a website prototype to help the managers of the Ta'aruf Padi Melati Forum to do matching Potential Pairing with the Application of the Cosine Similarity Algorithm. The application of the Cosine Similarity algorithm aims to compare the degree of fit of several candidates. The research method is carried out in several stages starting in stages, namely interviews with the managers of the jasmine rice ta'aruf forum, then conducting by applying the Cosine similarity method to create a classification of category pairs into groups according to the degree of similarity of the criteria. The final result is the degree of match of the pair criteria expected by each participant.